Study on Nutrient Intake, Physical Activities and Blood Properties among Elementary School Children in Fuji City - Akisada, Chiemi; Kondo, Sonoko; Fukino, Yoko; Makita, Kazuko; Oishi, Kunie (Eiyōgaku zasshi, 1997)
From the viewpoint of preventing adult-type diseases, factors related to obesity in children were examined according to their sex by conducting a cross-sectional study on their physical conditions, blood properties, nutritional status and daily habits by time study among sixth graders in Fuji City, Shizuoka. The following result was obtained. 1) Prevalence of obesity was 7.3% for boys and 11% for girls. Boys with high cholesterol accounted for 15.1% and high serum glucose 10.9%, and girls with high cholesterol 15.2% and high serum glucose 3.8% respectively. 2) Energy consumption per body weight was lower in obese children than in non-obese children for both boys and girls. 3) Obese boys tended to have breakfast or supper alone, and obese girls tended to get up late and go to bed late with less physical activities than non-obese girls. These habits may have influenced their obesity. 4) In the multiple regression analysis of obesity and blood pressure and hematology findings, obesity was positively correlated with systolic blood pressure while it was negatively correlated with HDL-cholesterol among boys as well as girls. 5) Obese children tended to show lower intake of calcium and vitamin A than nonobese children, but no other problems were found with them in terms of food sources or the intake of nutrient such as fat.